Menjelaskan Perumusan Tanggung Jawab Rekrutmen Sumber Daya Manusia - Naila Nasha Najwa Yofanda (Jurnal Riset Multidisiplin Edukasi, 2026)
Human resources (HR) are strategic assets that play a crucial role in determining organizational success. The effectiveness of human resource management is highly influenced by the recruitment process, which serves as the initial stage in acquiring qualified employees. Recruitment is not merely intended to fill vacant positions but also to ensure that organizations obtain individuals whose competencies, skills, and qualifications align with organizational needs. Therefore, the formulation of responsibilities in the recruitment process is essential to ensure that recruitment activities are conducted effectively, efficiently, transparently, and accountably. This article aims to explain the formulation of responsibilities in human resource recruitment by identifying the roles and responsibilities of the human resource department, line managers, and organizational leaders. The study employs a library research method with a qualitative descriptive approach using secondary data obtained from books, scientific journals, and other relevant academic sources. The results indicate that a clear division of responsibilities can improve coordination among stakeholders, minimize recruitment errors, enhance the quality of hiring decisions, and support organizational performance. In addition, technological developments have significantly influenced recruitment practices, requiring organizations to continuously adapt their recruitment systems and responsibilities to remain effective in attracting qualified candidates. Thus, a well-defined recruitment responsibility framework contributes to obtaining competent human resources and achieving sustainable organizational goals.